Measurement of the azimuthal anisotropy for charged particle production in root s(NN)=2.76 TeV lead-lead collisions with the ATLAS detector - Aad, G; Abbott, B; Abdallah, J; Khalek, SA; Abdelalim, A; Abdesselam, A; Abdinov, O; Abi, B; Abolins, M; AbouZeid, O; Abramowicz, H; Abreu, H; et al. (American Physical Society, 2012)
Differential √ measurements of charged particle azimuthal anisotropy are presented for lead-lead collisions at √sNN = 2.76 TeV with the ATLAS detector at the LHC, based on an integrated luminosity of approximately 8 μb-1. This anisotropy is characterized via a Fourier expansion of the distribution of charged particles in azimuthal angle relative to the reaction plane, with the coefficients νn denoting the magnitude of the anisotropy. Significant ν2-ν6 values are obtained as a function of transverse momentum (0.5 < pT < 20 GeV), pseudorapidity (|η| < 2.5), and centrality using an event plane method. The νn values for n ≥ 3 are found to vary weakly with both η and centrality, and their pT dependencies are found to follow an approximate scaling relation, ν n1/n (pT) ∝ ν 21/2 (pT), except in the top 5% most central collisions. A Fourier analysis of the charged particle pair distribution in relative azimuthal angle (Δφ = φa - φb) is performed to extract the coefficients νn,n = 〈cos nΔφ 〉. For pairs of charged particles with a large pseudorapidity gap (|Δη = ηa - ηb| > 2) and one particle with pT < 3 GeV, the ν2,2-ν6,6 values are found to factorize as νn,n(pTa, pTb) ≈ νn(pTa)νn(pTb) in central and midcentral events. Such factorization suggests that these values of ν2,2-ν6,6 are primarily attributable to the response of the created matter to the fluctuations in the geometry of the initial state. A detailed study shows that the ν1,1(pTa, pTb) data are consistent with the combined contributions from a rapidity-even ν1 and global momentum conservation.A two-component fit is used to extract the ν1 contribution. The extracted ν1 isobserved to cross zero at pT ≈ 1.0 GeV, reaches a maximum at 4-5 GeV with a value comparable to that for ν3, and decreases at higher pT.